Function of Givu as Traditional Law of the Tau Taa Wana Tribe - Restu Monika Nia Betaubun; Moh. Nutfa; Endang Yuliasih; Rivaldhy N Muhammad (Faculty of Law, Musamus University, 2022)
This study aims to explain the function of Givu as customary law as well as an identity that is able to regulate social life in the Tau Taa Wana Tribe community. The research approach used is descriptive qualitative. There were 13 informants who were selected by purposive sampling. The data used include primary and secondary data through qualitative observations, in-depth interviews, focus group discussions, documentation and document studies. Data analysis is a qualitative analysis through an interactive model, namely data reduction, data presentation; and levers. The results of the study show that Givu is a customary law that is sourced from noble abstract values ​​and rules so that it becomes a guide for social behavior that is able to support social structures. The application of Givu is regulated through institutions such as regulating economic, political and social needs. Close relationship with Mogombo (deliberation) for customary law decisions against a disturbance that maintains the spirit of collectivity and is able to strengthen a participatory culture. The importance of external recognition and respect for Givu customary law as well as state recognition and protection for the existence of the Tau Taa Wana Tribe.